2016
DOI: 10.1002/lno.10289
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope fractionation in phytoplankton as a potential proxy for pH rather than for [CO2(aq)]: Observations from a carbonate lake

Abstract: The method of reconstructing paleoatmospheric CO2 levels using carbon isotope signatures of organic matter buried in sediments has been questioned due to the dubious foundation that carbon isotope fractionation during phytoplankton photosynthesis (εp) is controlled primarily by aquatic CO2 concentration ([CO2(aq)]). Consequently, what carbon isotope data from bulk sedimentary organic matter reflects is a puzzle. In this study, we determined the carbon isotope compositions of dissolved inorganic carbon and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The positive relationship between CO2 concentration and carbon isotope fractionation has been observed empirically for a variety of autotrophs (Freeman & Hayes, 1992;Hinga et al, 1994;Schubert & Jahren, 2012;Wilkes et al, 2018), including for cyanobacteria in particular (Eichner et al, 2015;Hurley et al, 2021). Other studies showed that photoautotrophs that grew under a lower pH, and thus a higher proportion of CO2, also exhibited higher carbon fractionation (Mizutani & Wada, 1982;Roeske & O'Leary, 1984;Wang, Yeager, & Lu, 2016;Yoshioka, 1997).…”
Section: Discussionmentioning
confidence: 83%
“…The positive relationship between CO2 concentration and carbon isotope fractionation has been observed empirically for a variety of autotrophs (Freeman & Hayes, 1992;Hinga et al, 1994;Schubert & Jahren, 2012;Wilkes et al, 2018), including for cyanobacteria in particular (Eichner et al, 2015;Hurley et al, 2021). Other studies showed that photoautotrophs that grew under a lower pH, and thus a higher proportion of CO2, also exhibited higher carbon fractionation (Mizutani & Wada, 1982;Roeske & O'Leary, 1984;Wang, Yeager, & Lu, 2016;Yoshioka, 1997).…”
Section: Discussionmentioning
confidence: 83%
“…If relationships between δ 13 C POC and [CO 2 ] aq are to be established in surface waters, then extended to the sediments as a paleo‐atmospheric tool, variations on the diel scale should be acknowledged and accounted for if possible. Furthermore, it may be that C acquisition by cyanobacteria may be more sensitive to pH, rather than CO 2 availability (Mangan et al ; Wang et al ), an argument that is supported by the fact that modeled ε p was most sensitive to F HCO3 , which is a function of pH. Care should thus be taken when interpreting sedimentary δ 13 C POC in the context of atmospheric CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Headspace and ambient samples were analyzed for CO 2 and CH 4 by GC at the Nanjing Institute of Geography and Limnology (NIGLAS), Chinese Academy of Sciences. In situ partial pressures were calculated from headspace concentrations using Henry's Law, along with a temperature dependent solubility according to Wanninkhof (1992). Ambient air passed through the soda lime scrubber was found to contain a small amount of CO 2 .…”
Section: Dissolved Gassesmentioning
confidence: 99%
“…Indeed, during the experiments, the ε CO2-POC values were not constant either in the ASW or in the NAT. Moreover, the presence of CCMs in diatoms allows the uptake of both CO , no fractionation occurs during the process of intracellular dehydration, making the substrate for photosynthesis 9-10‰ enriched than CO 2(aq) , thus affecting the resulting phytoplankton isotopic ε CO2-POC values [112]. In this process, pH was identified as an important controlling factor, since it regulates the level of CA activity, the induction of CCMs and affects carbon leakage from the cell in relation to the CO 2(aq) and HCO 3 − uptake and conversion [112].…”
Section: Phytoplankton Isotopic Fractionationmentioning
confidence: 99%
“…Moreover, the presence of CCMs in diatoms allows the uptake of both CO , no fractionation occurs during the process of intracellular dehydration, making the substrate for photosynthesis 9-10‰ enriched than CO 2(aq) , thus affecting the resulting phytoplankton isotopic ε CO2-POC values [112]. In this process, pH was identified as an important controlling factor, since it regulates the level of CA activity, the induction of CCMs and affects carbon leakage from the cell in relation to the CO 2(aq) and HCO 3 − uptake and conversion [112]. The increase in pH detected in both conditions during diatom growth has clearly moved the carbonate system equilibrium towards higher concentrations of bicarbonate; thus, both in the ASW and NAT, HCO 3 − should have played an important role as a photosynthetic substrate.…”
Section: Phytoplankton Isotopic Fractionationmentioning
confidence: 99%